PREVALENCE OF GENETIC SUSCEPTIBILITY FOR CELIAC DISEASE IN BLOOD DONORS IN SÃO PAULO, BRAZIL - MUNIZ,Janaína Guilhem (2016)
ABSTRACT Background Celiac disease is a permanent intolerance induced by gluten, which is expressed by T-cell mediated enteropathy, and has a high prevalence in the general population. There is evidence of a strong genetic predisposition to celiac disease. Objective To determine the prevalence of genetic markers HLA-DQ2 and HLA-DQ8 in blood donors from São Paulo and measure human recombinant tissue transglutaminase antibody IgA class in HLA-DQ2 and HLA-DQ8 positive donors. Methods A total of 404 blood donors from São Paulo city and Jundiaí were included in the study and signed the informed consent form. Information regarding diarrhea, constipation and abdominal pain in the last 3 months was collected. Determination of HLADQ2 and HLADQ8 alleles was performed in all participants and human recombinant tissue transglutaminase antibody class IgA was measured only in blood donors who presentedDQ2 and/or DQ8. Results HLADQ2 and/or HLADQ8 were positive in 49% (198/404) of subjects. Positive samples were associated with alleles DR3, DR4, DR7, DR11 and DR12. The most frequent genotype was DR4-DQ8, which was present in 13.6% of samples, followed by genotypes DR3-DQ2 and DR7-DQ2 with DQB1*02 in heterozygous, which were present in 10.4% and 8.7%, respectively. Eleven out of 198 positive donors (5%) were positive to human tissue transglutaminase test. Conclusion We observed a high prevalence of genetic markers for celiac disease, HLA-DQ2 and HLA-DQ8, in blood donors from São Paulo, similar to prevalence described in Europe. These findings show that the prevalence of celiac disease should not be rare in our country, but underdiagnosed.